Research progress on current status and influencing factors of oral health-related quality of life in adolescents (青少年口腔健康相关生活质量现状及影响因素研究进展) - HU Mengjiao (胡梦姣); YAO Lan (姚兰); DU Tonglin (杜永琳); WANG Ting (王婷) (Journal of International Translational Medicine Limited, 2023)
Research on oral health-related quality of life plays an important role in not only clinical practice but also public health decision-making. This paper reviewed studies on current status and influencing factors of oral health-related quality of life in adolescents, and provided reference for improve of oral healthcare and health-related quality in in adolescents. (口腔健康相关生活质量不仅对临床实践有重要意义, 而且对公共卫生工作的方针、政策的制定也有重要参考价值。本研究就青少年口腔健康相关生活质量现状以及影响因素进行综述, 旨在为提高青少年口腔健康相关生活质量提供理论依据。)